Associations between circulating carotenoids, genomic instability and the risk of high‐grade prostate cancer. Issue 4 (20th November 2015) - Nordström, Tobias; Van Blarigan, Erin L.; Ngo, Vy; Roy, Ritu; Weinberg, Vivian; Song, Xiaoling; Simko, Jeffry; Carroll, Peter R.; Chan, June M.; Paris, Pamela L.
Abstract : BACKGROUND: Carotenoids are a class of nutrients with antioxidant properties that have been purported to protect against cancer. However, the reported associations between carotenoids and prostate cancer have been heterogeneous and lacking data on interactions with nucleotide sequence variations and genomic biomarkers. OBJECTIVE: To examine the associations between carotenoid levels and the risk of high‐grade prostate cancer, also considering antioxidant‐related genes and tumor instability. METHODS: We measured plasma levels of carotenoids and genotyped 20 single nucleotide polymorphisms (SNP) in SOD1, SOD2, SOD3, XRCC1, and OGG1 among 559 men with non‐metastatic prostate cancer undergoing radical prostatectomy. We performed copy number analysis in a subset of these men (n = 67) to study tumor instability assessed as Fraction of the Genome Altered (FGA). We examined associations between carotenoids, genotypes, tumor instability and risk of high‐grade prostate cancer (Gleason grade ≥ 4 + 3) using logistic and linear regression. RESULTS: Circulating carotenoid levels were inversely associated with the risk of high‐grade prostate cancer; odds ratios (OR) and 95% confidence intervals (CI) comparing highest versus lowest quartiles were: 0.34 (95% CI: 0.18–0.66) for α‐carotene, 0.31 (95% CI: 0.15–0.63) for β‐carotene, 0.55 (0.28–1.08) for lycopene and 0.37 (0.18–0.75) for total carotenoids. SNPs rs25489 in XRCC1, rs699473 in SOD3 and rs1052133 in OGG1 modified these associations for α‐carotene, β‐carotene and lycopene, respectively ( P  ≤ 0.05). The proportion of men with a high degree of FGA increased with Gleason Score ( P  < 0.001). Among men with Gleason score ≤ 3 + 4, higher lycopene levels were associated with lower FGA ( P  = 0.04). CONCLUSION: Circulating carotenoids at diagnosis, particularly among men carrying specific somatic variations, were inversely associated with risk of high‐grade prostate cancer. In exploratory analyses, higher lycopene level was associated with less genomic instability among men with low‐grade disease which is novel and supports the hypothesis that lycopene may inhibit progression of prostate cancer early in its natural history. Prostate 76:339–348, 2016 . © 2015 Wiley Periodicals, Inc.